DAMPAK PEMBANGUNAN BANDARA INTERNASIONAL KERTAJATI DALAM KAJIAN GREEN POLITICAL THEORY - Hermanto, Bambang Hermanto (Jurusan Ilmu Sosial dan Ilmu Politik Fakultas Hukum Universitas Jambi, 2021)
One of the infrastructure development programs that has been launched by the Government of West Java Province is to develop the Kertajati area into an airport and aero-city area. The construction of Kertajati International Airport will trigger a very big change for the community. This study is important to do, bearing in mind that the successful development of Kertajati International Airport has a major impact on human life and the environment. This research uses a qualitative approach. The method used in this research is media analysis and literature study. Data collection techniques used are derived from primary data in the form of observations of phenomena that occur and secondary data in the form of valid documentation. Identification of the negative impacts of the conversion of agricultural land into Kertajati Airport from environmental aspects including the availability of water for agricultural land and noise. Agricultural land directly adjacent to the location of Kertajati International Airport is experiencing problems related to the disruption of waterways and water sources. Transfer of the function of agricultural land to Kertajati International Airport resulted in a decrease in environmental quality, so the impact on air pollution and quality for agriculture is worse. Noise is the most negative impact felt by people who live close to Kertajati International Airport. In the development of Kertajati International Airport, the state must provide opportunities for the collective citizens to participate in the processes of making public policies both ecocentrism and anthroprtrism (eco-democracy). Do not let the construction of Kertajati International Airport cause natural disasters, climate change, air pollution, and environmental destruction. The construction of the Kertajati International Airport must not be ecosentrism in nature, where the natural environment is maximally utilized to cause a crisis.